Detailed explanation of predicate logic

In order to solve the shortcomings of propositional logic, predicate logic was introduced

Predicate logic further analyzes simple propositions to find out the relationship between the described objects and objects.
For example: " 2 22 is an even number" can be generalized to "xxx is an even number”

predicate

Individual constants and individual variables

individual constant

Symbols used to represent specific or specific individuals are called individual constants , commonly used lowercase letters a, b, c, ⋯ a,b,c,\cdotsa,b,c, means

For example: " 2 22 2in " 2 is an even number"2 is the individual constant

individual variable
definition

Variables used to represent any individual are called individual variables , commonly used lowercase letters x, y, z, ⋯ x,y,z,\cdotsx,y,z, means

For example: " xxxxin " x is an even number"x is the individual variable

area of ​​study

The value range of an individual variable is called the domain of discourse or individual domain of the variable.

total individual domain

The set of all individuals that can be represented by all individual variables is called the total individual domain

definition

A pattern that describes the characteristics of a single individual (unary predicate) or the relationship between multiple individuals (multiple predicates) is called a predicate
, such as " ⋯ \cdots is an even number" is the predicate

  1. A unary predicate
    represents the characteristics of an individual, represented by an expression consisting of a capital letter expressing the individual characteristics and an individual constant or variable, such as P ( a ) P (a)P(a) P ( x ) P(x) P(x)
  2. Binary predicate
    represents the relationship between two individuals, expressed by an expression composed of a capital letter expressing the relationship between the two individuals and two individual constants or variables, such as P ( x , y ) P (x, y)P(x,y)
  3. n n n- ary predicate
    expressesnnThe relationship between n individuals is expressed as nThe capital letters and nn of the relationship between n individualsAn expression composed of n individual constants or variables, such asP ( x 1 , x 2 , ⋯ , xn ) P(x_1,x_2,\cdots,x_n)P(x1,x2,,xn)

The predicate can be regarded as a propositional function , assuming nnn -ary predicateP ( x 2 , x 2 , ⋯ , xn ) P(x_2,x_2,\cdots,x_n)P(x2,x2,,xn),其中 x 1 ∈ D 1 , x 2 ∈ D 2 , ⋯   , x n ∈ D n x_1\in D_1,x_2\in D_2,\cdots,x_n\in D_n x1D1,x2D2,,xnDn,则 P ( x 1 , x 2 , ⋯   , x n ) P(x_1,x_2,\cdots,x_n) P(x1,x2,,xn) can be regarded as starting from the setD 1 × D 2 × ⋯ × D n D_1\times D_2\times\cdots\times D_nD1×D2××Dnto the set { T , F } \{T,F\}{ T,The mapping of F }
is as shown below:
Insert image description here

It can be seen from the definition of predicate that predicate P ( x 1 , x 2 , ⋯ , xn ) P(x_1,x_2,\cdots,x_n)P(x1,x2,,xn) is just a function, so it has no true or false values. Only by substituting each individual variable into the determined individual constant in the corresponding individual domain can we obtain a proposition with a definite true or false value.

Propositions can be seen as special forms of predicates
when n = 0 n=0n=0 , predicatePPP degenerates into a proposition

characteristic predicate

Before understanding characteristic predicates, you need to understand quantization

introduction

For example, propositions: "All people are mortal", "Some people are not afraid of death",
suppose H (x) H(x)H ( x ) means "xxx is a person",D ( x ) D(x)D ( x ) means "xxx is mortal",F ( x ) F(x)F ( x ) means "xxx is not afraid of death"
will be symbolized below

  • If the domain of discussion is all human beings, the symbolic result is ∀ x D ( x ) \forall xD(x)xD(x) ∃ x F ( x ) \exists x F(x) xF(x)
  • If the domain of discussion is the domain of all individuals, the symbolic result is
    (1) "Everyone is mortal" which can be equivalently expressed as "For any xxx , ifxxx is a person, thenxxx is mortal"
    so the symbolic result is∀ x [ H ( x ) → D ( x ) ] \forall x[H(x)\rightarrow D(x)]x[H(x)D ( x )]
    (2) "Some people are not afraid of death" can be equivalently expressed as "there isxxx x x x is a person, andxxx is not afraid of death"
    so the symbolic result is∃ x [ H ( x ) ∧ D ( x ) ] \exists x[H(x)\land D(x)]x[H(x)D(x)]

For the example above, H ( x ) H(x)H ( x ) is called a characteristic predicate and is used to qualifyxxx is a person

definition

Characteristic predicates are used to limit the domain of discourse to individuals that satisfy the predicate.

rule

When adding characteristic predicates to formulas, the following two rules must be met:

  • For universal quantifiers, the characteristic predicate is added as the antecedent of the conditional
  • For existential quantifiers, the characteristic predicate is added as the conjunction of the conjunction

quantifier

Only predicates cannot express propositions such as "all people can breathe" and "some rational numbers are natural numbers". Quantifiers need to be introduced.

type

universal quantifier

Chinese expression "for any xxx ” can be written as∀ x \forall xx , where∀ \forall is calledthe universal quantifier,xxx is called a quantifier∀ \forall 'saction variableorguidance variable

For example: ∀ x P ( x ) \forall xP(x)x P ( x ) means “for allxxx hasP ( x ) P(x)P(x)

existential quantifier

Chinese expression "there is a certain xx"x ” can be written as∃ x \exists xx , where∃ \exists is calledan existential quantifier,xxx is called a quantifier∃ \exists ’saction variableorguidance variable

如: ∃ x P ( x ) \exists xP(x) x P ( x ) means “there is a certainxxx satisfiesP ( x ) P(x)P(x)

Quantify

definition

In the predicate P ( x ) P(x)P ( x ) is preceded by the universal quantifier∀ x \forall xx or existential quantifier∃ x \exists xx is calledthe individual variable xxx is quantified by a universal quantifier or an existential quantifier, if it isPPP specifies the specific meaning, which isxxx specifies the domain of discussion, then∀ x P ( x ) \forall xP(x)xP(x) ∃ x P ( x ) \exists xP(x) xP(x) 成为一个具有真假值的命题

量化后所得命题的真值与个体变元的论域有关,如 ∃ x ( x = 3 ) \exists x(x=3) x(x=3);如果论域为自然数则为真,如果论域为负整数则为假
为统一表述,若不加说明,则默认都为全总个体域

量化的命题形式表示

如果论域是有限集合,则对于某一个体变元的量化可以用命题形式表示

设论域 D = { a 1 , a 2 , ⋯   , a n } D=\{a_1,a_2,\cdots,a_n\} D={ a1,a2,,an},则有

  • ∀ x P ( x ) ⇔ P ( a 1 ) ∧ P ( a 2 ) ∧ ⋯ ∧ P ( a n ) \forall xP(x)\Leftrightarrow P(a_1)\land P(a_2)\land\cdots\land P(a_n) xP(x)P(a1)P(a2)P(an)
  • ∃ x P ( x ) ⇔ P ( a 1 ) ∨ P ( a 2 ) ∨ ⋯ ∨ P ( a n ) \exists xP(x)\Leftrightarrow P(a_1)\lor P(a_2)\lor\cdots\lor P(a_n) xP(x)P(a1)P(a2)P(an)

Jurisdiction

Before understanding the scope of quantifiers, you need to understand the predicate formula first

definition

In the predicate formula, the scope of the quantifier is called the scope of the quantifier , also known as the scope of the quantifier.

  • If the quantifier is followed by only an atomic predicate formula, the scope of the quantifier is the atomic predicate formula,
    such as: ∀ x P ( x ) \forall xP(x) x in ∀ x P ( x ) \forall x The domain of x is P ( x ) P(x)P(x)
  • If the quantifier is followed by brackets, the area represented by the brackets is the scope of the quantifier.
    For example: ∃ x ( P ( x ) → Q ( x ) ) \exists x(P(x)\rightarrow Q(x))x(P(x)∃ x \exists xin Q ( x ))The domain ofx is ( P ( x ) → Q ( x ) ) (P(x)\rightarrow Q(x))(P(x)Q(x))
  • If multiple quantifiers appear next to each other, the following quantifier and its scope are the scope of the previous quantifier.
    For example: ∀ x ∃ y P ( x , y ) \forall x\exists y P(x,y)xyP(x,y) 中的 ∃ y \exists y The domain of y is P ( x , y ) P(x,y)P(x,y) ∀ x \forall x The domain ofx is ∃ y P ( x , y ) \exists y P(x,y)yP(x,y)
constraint appears
definition

In the quantifier ∀ x \forall xx ∃ x \exists x xx within the jurisdiction ofxAll occurrences of x are called constrained occurrences

constraint variables

The individual variables in which a constraint occurs are called constraint variables

free variable

Individual variables that do not appear as constraints are called free variables

For example: predicate formula ∀ x P ( x , y ) \forall x P(x,y)xP(x,xxin y )x is the constraint variable;yyy free variable

predicate formula

atomic formula

A single predicate without connectives and quantifiers is called the atomic formula
of predicate calculus , such as: P ( x 1 , x 2 , ⋯ , xn ) ( n ≥ 0 ) P(x_1,x_2,\cdots,x_n)~~~~ (n\geq 0)P(x1,x2,,xn)    (n0)

Because the proposition is the predicate n = 0 n=0n=A special form of 0 , so that individual propositional constants and propositional variables are atomic formulas of the predicate calculus

definition

Predicate formula , also known as the well-formed formula of predicate logic , the following is its recursive definition

  1. Basic clause: Atomic formulas are predicate formulas
  2. induction clause
    • Young AAA is a predicate formula, then¬ A \lnot A¬ A is a predicate formula
    • Young A, BA,BA,B is a predicate formula, thenA ∧ BA\land BAB A ∨ B A\lor B AB A → B A\rightarrow B AB A ↔ B A\leftrightarrow B AB 是谓词公式
    • A A A 是谓词公式,且 A A A 中的个体变元 x x x 未被量词量化,则量化后 ∀ x A ( x ) \forall xA(x) xA(x) ∃ x A ( x ) \exists xA(x) xA(x) 是量词公式
  3. 极小性条款:只有有限次地应用条款 1 和条款 2 生成的表达式才是谓词公式

由定义知所有的命题公式都是谓词公式

子公式

B B B 是谓词公式 A A A子公式的定义如下

  • B B B A A A 的连续段
  • B B B 是谓词公式

赋值

对谓词公式赋值需要完成以下操作:

  1. 指定论域 E E E
  2. 指定谓词符的含义
  3. Specify definite propositions for propositional arguments
  4. Specify individuals on the universe of discussion for free variables

Note : Constraint variables do not need to be specified

Eishin official

Generalization of Equivalence and Implication Formulas in Propositional Logic

Apply the substitution rule to the equivalence or implication in propositional logic and substitute it with the predicate formula in predicate logic. The resulting formula is the equivalence or implication of the predicate formula.

For example: proposition formula equivalence P → Q ⇔ ¬ P ∨ QP\rightarrow Q\Leftrightarrow\lnot P\lor QPQ¬PThe generalization of Q in predicate logic is
∀ x P ( x ) → ∃ x Q ( x ) ⇔ ¬ ∀ x P ( x ) ∨ ∃ x Q ( x ) \forall xP(x)\rightarrow \exists xQ(x)\ Leftrightarrow \lnot\forall xP(x)\lor \exists xQ(x)xP(x)xQ(x)¬∀xP(x)xQ(x)

Negation law of quantifiers
  • ¬ ∀ x P ( x ) ⇔ ∃ x ¬ P ( x ) \lnot\forall xP(x)\Leftrightarrow \exists x\lnot P(x) ¬∀xP(x)x ¬ P ( x )
    means “not allxxx all satisfiesP ( x ) P(x)P ( x ) ” can be said to be “there isxxx satisfies non-P ( x ) P(x)P(x)
  • ¬ ∃ x P ( x ) ⇔ ∀ x ¬ P ( x ) \lnot\exists xP(x)\Leftrightarrow\forall x\lnot P(x) ¬∃xP(x)x ¬ P ( x ) means “ xx
    does not exist"x satisfies $P(x)" can be said to be "for allxxx all satisfies non-P ( x ) P(x)P(x)
Laws of Expansion and Contraction of Quantifier Scope
  • ∀ x ( P ( x ) ∧ Q ) ⇔ ∀ x P ( x ) ∧ Q \forall x(P(x)\land Q)\Leftrightarrow\forall xP(x)\land Q x(P(x)Q)xP(x)Q
    ∃ x ( P ( x ) ∧ Q ) ⇔ ∃ x P ( x ) ∧ Q \exists x(P(x)\land Q)\Leftrightarrow\exists xP(x)\land Q x(P(x)Q)xP(x)Q
    ∀ x ( P ( x ) ∨ Q ) ⇔ ∀ x P ( x ) ∨ Q \forall x(P(x)\lor Q)\Leftrightarrow\forall xP(x)\lor Q x(P(x)Q)xP(x)Q
    ∃ x ( P ( x ) ∨ Q ) ⇔ ∃ x P ( x ) ∨ Q \exists x(P(x)\lor Q)\Leftrightarrow\exists xP(x)\lor Q x(P(x)Q)xP(x)Q

  • ∀ x P ( x ) → Q ⇔ ∃ x ( P ( x ) → Q ) \forall xP(x)\rightarrow Q\Leftrightarrow\exists x(P(x)\rightarrow Q) xP(x)Qx(P(x)Q)
    ∃ x P ( x ) → Q ⇔ ∀ x ( P ( x ) → Q ) \exists xP(x)\rightarrow Q\Leftrightarrow\forall x(P(x)\rightarrow Q) xP(x)Qx(P(x)Q)

    proving process

    Prove below that ∀ x P ( x ) → Q ⇔ ∃ x ( P ( x ) → Q ) \forall xP(x)\rightarrow Q\Leftrightarrow\exists x(P(x)\rightarrow Q)xP(x)Qx(P(x)Q)
    ∀ x P ( x ) → Q ⇔ ¬ ∀ x P ( x ) ∨ Q ⇔ ∃ x ¬ P ( x ) ∨ Q ⇔ ∃ x ( ¬ P ( x ) ∨ Q ) ⇔ ∃ x ( P ( x ) → Q ) \begin{aligned} \forall xP(x)\rightarrow Q&\Leftrightarrow\lnot\forall xP(x)\lor Q\\ &\Leftrightarrow\exists x\lnot P(x)\lor Q\\ &\Leftrightarrow\exists x(\lnot P(x)\lor Q)\\ &\Leftrightarrow\exists x(P(x)\rightarrow Q) \end{aligned} xP(x)Q¬∀xP(x)Qx¬P(x)Qx(¬P(x)Q)x(P(x)Q)

  • Q → ∀ x P ( x ) ⇔ ∀ x ( Q → P ( x ) ) Q\rightarrow\forall xP(x)\Leftrightarrow\forall x(Q\rightarrow P(x)) QxP(x)x(QP(x))
    Q → ∃ x P ( x ) ⇔ ∃ x ( Q → P ( x ) ) Q\rightarrow\exists xP(x)\Leftrightarrow\exists x(Q\rightarrow P(x)) QxP(x)x(QP(x))

distributive law of quantifiers
  • ∀ x ( P ( x ) ∧ Q ( x ) ) ⇔ ∀ x P ( x ) ∧ ∀ x Q ( x ) \forall x(P(x)\land Q(x))\Leftrightarrow\forall xP(x)\land\forall xQ(x) x(P(x)Q(x))xP(x)xQ(x)
    ∃ x ( P ( x ) ∨ Q ( x ) ) ⇔ ∃ x P ( x ) ∨ ∃ x Q ( x ) \exists x(P(x)\lor Q(x))\Leftrightarrow\exists xP(x)\lor\exists xQ(x) x(P(x)Q(x))xP(x)xQ(x)

    proving process

    Prove below that ∀ x ( P ( x ) ∧ Q ( x ) ) ⇔ ∀ x P ( x ) ∧ ∀ x Q ( x ) \forall x(P(x)\land Q(x))\Leftrightarrow\forall xP( x)\land\forall xQ(x)x(P(x)Q(x))xP(x)xQ(x)
    ∃ x ( P ( x ) ∨ Q ( x ) ) ⇔ ∃ x P ( x ) ∨ ∃ x Q ( x ) \exists x(P(x)\lor Q(x))\Leftrightarrow\exists xP(x)\lor\exists xQ(x) x(P(x)Q(x))xP(x)x Q ( x ) can be proved in the same way. Suppose
    the domain of discussion isDDD
    ∀ x ( P ( x ) ∧ Q ( x ) ) \forall x(P(x)\land Q(x)) x(P(x)When Q ( x )) is true, that is, for alla ∈ D a\in DaD hasP ( a ) ∧ Q ( a ) P(a)\land Q(a)P(a)Q ( a ) below∴
    P ( a ) \therefore P(a)P(a) Q ( a ) Q(a) Q ( a ) are all true
    ∴ ∀ x P ( x ) \therefore\forall xP(x)xP(x) ∀ x Q ( x ) \forall xQ(x) x Q ( x ) are all true
    ∴ ∀ x P ( x ) ∧ ∀ x Q ( x ) \therefore\forall xP(x)\land\forall xQ(x)xP(x)x Q ( x ) is true
    when∀ x ( P ( x ) ∧ Q ( x ) ) \forall x(P(x)\land Q(x))x(P(x)When Q ( x )) is false, there existsa ∈ D a\in DaD 使 P ( a ) ∧ Q ( a ) P(a)\land Q(a) P(a)Q ( a ) if∴
    P ( a ) \therefore P(a)P(a) Q ( a ) Q(a) At least one of Q ( a ) is false. Let us assume thatP ( a ) P(a)P ( a ) is false, then∀ x P ( x ) \forall xP(x)x P ( x ) is false
    ∴ x P ( x ) ∧ x Q ( x ) \therefore xP(x)\land xQ(x)xP(x)x Q ( x ) is false
    so∀ x ( P ( x ) ∧ Q ( x ) ) \forall x(P(x)\land Q(x))x(P(x)Q(x)) ∀ x P ( x ) ∧ ∀ x Q ( x ) \forall xP(x)\land\forall xQ(x) xP(x)xQ(x) 真值相同
    ∀ x ( P ( x ) ∧ Q ( x ) ) ⇔ ∀ x P ( x ) ∧ ∀ x Q ( x ) \forall x(P(x)\land Q(x))\Leftrightarrow\forall xP(x)\land\forall xQ(x) x(P(x)Q(x))xP(x)xQ(x)

  • ∀ x P ( x ) ∨ ∀ x Q ( x ) ⇒ ∀ x ( P ( x ) ∨ Q ( x ) ) \forall xP(x)\lor\forall xQ(x)\Rightarrow\forall x(P(x)\lor Q(x)) xP(x)xQ(x)x(P(x)Q(x))
    ∃ x ( P ( x ) ∧ Q ( x ) ) ⇒ ∃ x P ( x ) ∧ ∃ x Q ( x ) \exists x(P(x)\land Q(x))\Rightarrow\exists xP(x)\land\exists xQ(x) x(P(x)Q(x))xP(x)xQ(x)

    proving process

    Prove below that ∀ x P ( x ) ∨ ∀ x Q ( x ) ⇒ ∀ x ( P ( x ) ∨ Q ( x ) ) \forall xP(x)\lor\forall xQ(x)\Rightarrow\forall x(P (x)\lor Q(x))xP(x)xQ(x)x(P(x)Q(x))
    ∃ x ( P ( x ) ∧ Q ( x ) ) ⇒ ∃ x P ( x ) ∧ ∃ x Q ( x ) \exists x(P(x)\land Q(x))\Rightarrow\exists xP(x)\land\exists xQ(x) x(P(x)Q(x))xP(x)x Q ( x ) can be proved in the same way
    . Let’s assume that the domain of discussion isDDD
    ∀ x P ( x ) ∨ ∀ x Q ( x ) \forall xP(x)\lor\forall xQ(x) xP(x)When ∀ x Q ( x ) is true,∀ x P ( x ) \forall xP(x)xP(x) ∀ x Q ( x ) \forall xQ(x) At least one ofx Q ( x )
    is true . Let∀ x P ( x ) \forall xP(x)x P ( x ) is true, that is, for alla ∈ D a\in DaD , both haveP ( a ) P(a)P(a) 为真
    ∴ P ( a ) ∨ Q ( x ) \therefore P(a)\lor Q(x) P(a)Q(x) 为真
    ∴ ∀ x ( P ( x ) ∨ Q ( x ) ) \therefore\forall x(P(x)\lor Q(x)) x(P(x)Q(x)) 为真
    肯定前件法 ∀ x P ( x ) ∨ ∀ x Q ( x ) ⇒ ∀ x ( P ( x ) ∨ Q ( x ) ) \forall xP(x)\lor\forall xQ(x)\Rightarrow\forall x(P(x)\lor Q(x)) xP(x)xQ(x)x(P(x)Q(x))
    ∀ x ( P ( x ) ∨ Q ( x ) ) \forall x(P(x)\lor Q(x)) x(P(x)Q ( x )) is true, that is, for alla ∈ D a\in DaD , both haveP ( a ) ∨ Q ( a ) P(a)\lor Q(a)P(a)Q ( a ) is true
    but it does not necessarily have∀ x P ( x ) ∨ ∀ x Q ( x ) \forall xP(x)\lor\forall xQ(x)xP(x)x Q ( x ) is true
    becauseD = { a , b } D=\{a,b\}D={ a,b} P ( a ) P(a) P ( a ) is true,Q ( a ) Q(a)Q ( a ) is false;P ( b ) P(b)P ( b ) is false,Q ( b ) Q(b)When Q ( b ) is true, ∀ x ( P ( x ) ∨ Q ( x ) ) \forall x(P(x)\lor Q(x))x(P(x)Q ( x )) is true, but∀ x P ( x ) ∨ ∀ x Q ( x ) \forall xP(x)\lor\forall xQ(x)xP(x)x Q ( x ) is false

  • ∀ x ( P ( x ) → Q ( x ) ) ⇒ ∀ x P ( x ) → ∀ x Q ( x ) \forall x(P(x)\rightarrow Q(x))\Rightarrow \forall xP(x)\rightarrow\forall xQ(x) x(P(x)Q(x))xP(x)xQ(x)
    ∀ x ( P ( x ) ↔ Q ( x ) ) ⇒ ∀ x P ( x ) ↔ ∀ x Q ( x ) \forall x(P(x)\leftrightarrow Q(x))\Rightarrow\forall xP(x)\leftrightarrow\forall xQ(x) x(P(x)Q(x))xP(x)xQ(x)

    proving process

    对于 ∀ x ( P ( x ) → Q ( x ) ) ⇒ ∀ x P ( x ) → ∀ x Q ( x ) \forall x(P(x)\rightarrow Q(x))\Rightarrow \forall xP(x)\rightarrow\forall xQ(x) x(P(x)Q(x))xP(x)xQ(x)
    这里用否定后件法证明
    不妨设论域为 D D D
    ∀ x P ( x ) → ∀ x Q ( x ) \forall xP(x)\rightarrow\forall xQ(x) xP(x)xQ(x) 为假时, ∀ x P ( x ) \forall xP(x) xP(x) 为真、 ∀ x Q ( x ) \forall xQ(x) xQ(x) 为假
    因此,存在 a ∈ D a\in D aD 使 P ( a ) P(a) P(a) 为真、 Q ( a ) Q(a) Q ( a ) is false.
    Therefore,∀ x ( P ( x ) → Q ( x ) ) \forall x(P(x)\rightarrow Q(x))x(P(x)Q ( x )) is false

    对于 ∀ x ( P ( x ) ↔ Q ( x ) ) ⇒ ∀ x P ( x ) ↔ ∀ x Q ( x ) \forall x(P(x)\leftrightarrow Q(x))\Rightarrow\forall xP(x)\leftrightarrow\forall xQ(x) x(P(x)Q(x))xP(x)xQ(x)
    ∀ x ( P ( x ) ↔ Q ( x ) ) ⇔ ∀ x [ ( P ( x ) → Q ( x ) ) ∧ ( Q ( x ) → P ( x ) ) ] ⇔ ∀ x ( P ( x ) → Q ( x ) ) ∧ ∀ x ( Q ( x ) → P ( x ) ) ⇒ ( ∀ x P ( x ) → ∀ x Q ( x ) ) ∧ ( ∀ x Q ( x ) → ∀ x P ( x ) ) ⇔ ∀ x P ( x ) ↔ ∀ x Q ( x ) \begin{aligned} \forall x(P(x)\leftrightarrow Q(x))&\Leftrightarrow\forall x[(P(x)\rightarrow Q(x))\land(Q(x)\rightarrow P(x))]\\ &\Leftrightarrow\forall x(P(x)\rightarrow Q(x))\land\forall x(Q(x)\rightarrow P(x))\\ &\Rightarrow(\forall xP(x)\rightarrow\forall xQ(x))\land(\forall xQ(x)\rightarrow\forall xP(x))\\ &\Leftrightarrow\forall xP(x)\leftrightarrow\forall xQ(x) \end{aligned} x(P(x)Q(x))x[(P(x)Q(x))(Q(x)P(x))]x(P(x)Q(x))x(Q(x)P(x))(xP(x)xQ(x))(xQ(x)xP(x))xP(x)xQ(x)

  • ∃ x ( P ( x ) → Q ( x ) ) ⇔ ∀ x P ( x ) → ∃ x Q ( x ) \exists x(P(x)\rightarrow Q(x))\Leftrightarrow\forall xP(x)\rightarrow\exists xQ(x) x(P(x)Q(x))xP(x)xQ(x)
    ∃ x P ( x ) → ∀ x Q ( x ) ⇒ ∀ x ( P ( x ) → Q ( x ) ) \exists xP(x)\rightarrow\forall xQ(x)\Rightarrow\forall x(P(x)\rightarrow Q(x)) xP(x)xQ(x)x(P(x)Q(x))

    proving process

    下面证明 ∃ x ( P ( x ) → Q ( x ) ) ⇔ ∀ x P ( x ) → ∃ x Q ( x ) \exists x(P(x)\rightarrow Q(x))\Leftrightarrow\forall xP(x)\rightarrow\exists xQ(x) x(P(x)Q(x))xP(x)xQ(x)
    ∃ x ( P ( x ) → Q ( x ) ) ⇔ ∃ x ( ¬ P ( x ) ∨ Q ( x ) ) ⇔ ∃ x ¬ P ( x ) ∨ ∃ x Q ( x ) ⇔ ¬ ∀ x P ( x ) ∨ ∃ x Q ( x ) ⇔ ∀ x P ( x ) → ∃ x Q ( x ) \begin{aligned} \exists x(P(x)\rightarrow Q(x))&\Leftrightarrow\exists x(\lnot P(x)\lor Q(x))\\ &\Leftrightarrow\exists x\lnot P(x)\lor\exists xQ(x)\\ &\Leftrightarrow\lnot\forall xP(x)\lor\exists xQ(x)\\ &\Leftrightarrow\forall xP(x)\rightarrow\exists xQ(x) \end{aligned} x(P(x)Q(x))x(¬P(x)Q(x))x¬P(x)xQ(x)¬∀xP(x)xQ(x)xP(x)xQ(x)

    下面证明 ∃ x P ( x ) → ∀ x Q ( x ) ⇒ ∀ x ( P ( x ) → Q ( x ) ) \exists xP(x)\rightarrow\forall xQ(x)\Rightarrow\forall x(P(x)\rightarrow Q(x)) xP(x)xQ(x)x(P(x)Q(x))
    ∃ x P ( x ) → ∀ x Q ( x ) ⇔ ∀ x ¬ P ( x ) ∨ ∀ x Q ( x ) ⇒ ∀ x ( ¬ P ( x ) ∨ Q ( x ) ) ⇔ ∀ x ( P ( x ) → Q ( x ) ) \begin{aligned} \exists xP(x)\rightarrow\forall xQ(x)&\Leftrightarrow\forall x\lnot P(x)\lor\forall xQ(x)\\ &\Rightarrow\forall x(\lnot P(x)\lor Q(x))\\ &\Leftrightarrow\forall x(P(x)\rightarrow Q(x)) \end{aligned} xP(x)xQ(x)x¬P(x)xQ(x)x(¬P(x)Q(x))x(P(x)Q(x))

multi-weighted lexicon
  • ∀ x ∀ y P ( x , y ) ⇔ ∀ y ∀ x P ( x , y ) \forall x\forall yP(x,y)\Leftrightarrow\forall y\forall xP(x,y) xyP(x,y)yxP(x,y)
    ∃ x ∃ y P ( x , y ) ⇔ ∃ y ∃ x P ( x , y ) \exists x\exists yP(x,y)\Leftrightarrow\exists y\exists xP(x,y) xyP(x,y)yxP(x,y)
  • ∃ x ∀ y P ( x , y ) ⇒ ∀ y ∃ x P ( x , y ) \exists x\forall yP(x,y)\Rightarrow\forall y\exists xP(x,y) xyP(x,y)yxP(x,y)
    ∀ x ∃ y P ( x , y ) ⇒ ∃ y ∃ x P ( x , y ) \forall x\exists yP(x,y)\Rightarrow\exists y\exists xP(x,y) xyP(x,y)yxP(x,y)

The two variables can be visually demonstrated by the following figure:
Insert image description here

Inference theory of predicate logic

inference rules

The inference rules of propositional logic also apply to predicate logic, but in the reasoning process of predicate logic, it is sometimes necessary to eliminate or introduce quantifiers

Eliminate quantifier

When eliminating quantifiers, exist designation comes first and then full name designation

There is a specified rule

There is an existential specification , abbreviated as ES, as follows
∃ x P ( x ) ∴ P ( a ) \frac{\exists xP(x)}{\therefore P(a)}P(a)xP(x)
Among them, PPP is the predicate,aaa is in the domain of discourse such thatP ( a ) P(a)Individuals where P ( a ) is true

The meaning of this rule is: if ∃ x P ( x ) \exists xP(x)x P ( x ) is true, then there is an individual constantaaa ,fromP ( a ) P(a)P ( a ) is true

Full name designation rules

The full name specification (universal specification) , abbreviated as US, is as follows
∀ x P ( x ) ∴ P ( y ) \frac{\forall xP(x)}{\therefore P(y)}P ( y )xP(x)
Among them, PPP is the predicate,yyy is a free variable

The meaning of this rule is: if ∀ x P ( x ) \forall xP(x)x P ( x ) is true, then for any individual constantaaa , both haveP ( a ) P(a)P ( a ) is true

Introduce quantifiers
There are promotion rules

There is an existential generalization rule , abbreviated as EG, as follows
P ( a ) ∴ ∃ x P ( x ) \frac{P(a)}{\therefore \exists xP(x)}xP(x)P(a)
Among them, PPP is the predicate,aaa is in the domain of discourse such thatP ( a ) P(a)Individuals where P ( a ) is true

The meaning of this rule is: if there is an individual constant aa in the domain of discoursea ,fromP ( a ) P(a)P ( a ) is true, then∃ x P ( x ) \exists xP(x)x P ( x ) is true

Full name promotion rules

The full name is universal generalization , abbreviated as UG, as follows
Γ ⇒ P ( y ) ∴ Γ ⇒ ∀ x P ( x ) \frac{\Gamma\Rightarrow P(y)}{\therefore\Gamma\Rightarrow\forall xP (x)}CxP(x)CP ( y )
Among them, Γ \GammaΓ is the conjunction of known axioms and premises,PPP is the predicate,yyy is a free variable

The meaning of this rule is: if Γ \GammaΓ can be derived for any individualyyy hasP ( y ) P(y)P ( y ) is true, then∀ x P ( x ) \forall xP(x)x P ( x ) is true

reference

[1] Discrete Mathematics Xi'an University of Electronic Science and Technology Press Second Edition
[2] CSDN Blog

Guess you like

Origin blog.csdn.net/qq_52554169/article/details/132295606